Subordinate Clauses In The Boscombe Valley Short Story - Indriyani Ni Komang; Wahyu Nugraha Putra I Gusti Bagus; Deni Aryaningsih Ni Nyoman (ELYSIAN JOURNAL : English Literature, Linguistics and Translation Studies, 2021)
This study analyzed the types of subordinate clause in complex sentence found in The Boscombe Valley Short Story and the constituent structure of the subordinate clause. There are 21 data of complex sentences found in the The Boscombe Valley. The finding shows that there are three types of subordinate clause, which is the clause most frequently used is relative clause with 9 data or 43% of the total data it uses who, whose, that, and which as complementizer then followed by complement clause with 7 data or 33% of the total data which used that as complementizer and the least frequently clause is adverbial clause with 5 data or 24% of the total data it uses if and when as complemenntizer. And then the analysis of the constituent structure the researcher found that complement clause is marked when the verb (V) in main clause equals with the subordinate clause, it means this clause modifies the verb of main clause. While in relative clause when the Noun (N) in noun phrase equals with subordinate clause that means the clause modifies the noun. And adverbial clause is when the subordinate clause has modifies a whole clause or the whole sentence.